Analyzing factors towards adopting ICT within supply network in the UK - Musa, Haslinda (Penerbit UTeM, 2014)
Literature has shown that Information and Communication Technology (ICT) had been a potential source of disruption to business and at the same time ICT might be advantageous in supporting business at risk. Data from a questionnaire survey of 110 organizations across various sectors in the United Kingdom (UK) are used to answer the research question: “what are the key determinants to the adoption of ICT in an organization within its supply network?” The data collected were analyzed quantitatively, from simple analyses such as mean scores, and Spearman correlation coefficients, to more sophisticated analysis such as factor analysis, ANOVA, and logistic regression. Adoption level is predicted by a model with three (3) categories of independent variables including (i) the characteristics of ICT; including, the relative advantage, complexity, compatibility, and observability), (ii) the internal and external factors of innovation characteristics (managers’ support, strategy integration, and stakeholders pressure on the innovation), and (iii) the external environment (stakeholders pressure, system openness, environmental uncertainties and supply chain complexity). The main findings revealed that the adoption behavior in organizations within the supply chain can be understood from the model developed in this study. The most significant predictors of the adoption level of ICT are relative advantage, managers’ support, and system openness.